2010
DOI: 10.1002/ddr.20390
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic limitations of the use of nucleoside analogs in cancer therapy may be overcome by application of nanoparticles as drug carriers: A review

Abstract: Purine and pyrimidine nucleoside analogs (NAs) are antimetabolites commonly used in cancer therapy. Administered as prodrugs, NAs permeate the mambrane using specialized transporters. Following phosphorylation, they interfere with multiple cellular pocessess inducing cytotoxicity. Toxic effects of NAs are dependent on metabolic conversion from a prodrug into the active form. For instance, an exceptionally high activity of deoxycytidine kinase (dCK) in lymphocytes is correlated with a good therapeutic effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…Nucleoside analogues are an important class of chemotherapeutic agents used in the treatment of cancer and viral infections [ 23 , 24 , 25 ]. This study identified novel nucleoside analogues that proved to be cytotoxic and able to induce an unusual apoptotic response with the concurrent formation of cytoplasmic vacuoles in two colorectal adenocarcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside analogues are an important class of chemotherapeutic agents used in the treatment of cancer and viral infections [ 23 , 24 , 25 ]. This study identified novel nucleoside analogues that proved to be cytotoxic and able to induce an unusual apoptotic response with the concurrent formation of cytoplasmic vacuoles in two colorectal adenocarcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…They penetrate into the cell through nucleoside transporters (NTs). 12,13 Then, in a cell, NAs are phosphorylated by deoxycitidine kinase (dCK), monophosphate kinases (NMPKs) and diphosphate kinases (NDPKs) to 5 0 -mono-, diand triphosphates. 1,2,4 All NAs have a similar mechanism of activity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This results in serious side effects on other critical normal tissues such as bone marrow, kidney, liver and cardiac tissues. 12 Therefore, searching for novel approach for safe and accurate diagnosis of earlystage cancer and targeted therapies has been exciting yet challenging area of research.…”
Section: Introductionmentioning
confidence: 99%